The Ottawa Treaty on the path to customary law status - Bārene, Laura (Riga Graduate School of Law, 2020)
The main objective of this thesis is whether the Ottawa Treaty provisions have acquired the status of customary law and if not, whether it could over time. The thesis shows that while currently the Ottawa Treaty provisions do not have the status of a customary norm; it has potential of evolving into one. The topic is of great significance since anti-personnel landmines have an indefinite lifespan, meaning that they have been terrorizing generations since World War I and that they cost not only lives of innocent people but also affects the economy of states.
Keywords: Research Subject Categories::LAW/JURISPRUDENCE::Other law::International law; Customary law